High expression of DNMT3A and DNMT3B regulatory factors of TGFB in non-neoplastic liver tissues of HCC: DNMT3A and DNMT3B in Hepatocellular Carcinomas - Hu, Shifeng; Luo, Xuelian; Qian, Jun; Hou, Yujie; Shi, Wei (Cellular and Molecular Biology, 2023)
Increased expression of TGFB regulatory factors DNMT3A and DNMT3B in non-neoplastic liver tissues of HCC patients is the goal of this study. Furthermore, we demonstrate that TGF- is capable of elevating the percentage of CD133+ cells present in liver cancer cell lines in a manner that is both consistent and long-lasting over several cell divisions. This process is linked to stable alterations in DNA methylation that occur over the whole of the genome and continue even after cell division. In addition, the silencing of de novo DNA methyl-transferases with siRNA is able to inhibit the phenotypic changes that are induced by TGF-. According to the findings of our research, there is a self-sustaining interaction between the DNA methylation machinery and the TGF- signaling pathway, which may be significant in the development of cellular phenotypes. CD133 positive and negative fractions expand within liver cancer cell lines in proportions that remain stable throughout time. In contrast to their CD133- counterparts, MACS-sorted CD133+ Huh7cells demonstrated the ability to shape themselves into spheres when grown under non-attachment circumstances. This study also found that the TGF- is responsible for the de novo induction of CD133, which is linked to an increase in the expression of DNMT3 genes and there is a correlation between the TGF—induced transition in the cell subpopulation and a distinct DNA methylome. TGF- has the potential to generate genome-wide alterations in DNA methylation, which ultimately leads to a persistent shift in the fraction of liver cancer cell subpopulations.